2009
DOI: 10.1001/archpediatrics.2008.564
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Booster Seat Education and Distribution Program in Child Care Centers on Child Restraint Use Among Children Aged 4 to 8 Years

Abstract: To compare child care center-based booster seat education and distribution with no intervention when implemented immediately after booster seat legislation. Design: Cluster randomized controlled trial. Setting: Thirty-nine urban child care centers. Participants: Eight hundred fifty-four parents and 1010 children aged 4 to 8 years in vehicles leaving centers. Intervention: We trained 168 staff members at 20 centers to give parents and children messages promoting booster seats and supplied lesson plans, children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…Furthermore, one study trialed a multifaceted approach yet did not find a positive outcome. The authors suggested that high staff and child turnover at the centers may have led to parents receiving inconsistent and infrequent child restraint messages, leading to attenuation of intervention effects (Thoreson et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, one study trialed a multifaceted approach yet did not find a positive outcome. The authors suggested that high staff and child turnover at the centers may have led to parents receiving inconsistent and infrequent child restraint messages, leading to attenuation of intervention effects (Thoreson et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that low rates of BPB use are related to differences in risk perception, awareness, knowledge, and parenting styles (Simpson et al 2002). Successful interventions reported to increase BPB use in this population include legislation, mass media education, and incentives or the distribution of free BPBs combined with caregiver education (Durbin and the Committee on Injury Violence and Poison Prevention 2011; Ebel et al 2003b;Ehiri et al 2006;Thoreson et al 2009;Winston, Kallan, et al 2007). Though these studies demonstrated that interventions could be successful in improving BPB in minority populations, the sustainability of these programs requires models that rely on community member delivery rather than dependence on researcher-led efforts.…”
Section: Introductionmentioning
confidence: 99%
“…Community-based models for injury prevention have become an accepted injury prevention strategy, but there are few well-controlled studies that have evaluated these programmes to increase child restraint use 2. A recent community-based programme to increase booster seat use was effective in an Hispanic community but not in a low-income community,3 and another booster seat programme based in day care centres showed an increase in knowledge about booster seats but did not result in increased use of booster seats 4…”
Section: Introductionmentioning
confidence: 99%